An Automated Assay for Growth Differentiation Factor 15. (1st March 2017) - Wollert, Kai C; Kempf, Tibor; Giannitsis, Evangelos; Bertsch, Thomas; Braun, Siegmund L; Maier, Harald; Reim, Manfred; Christenson, Robert H
Abstract: Background: Growth differentiation factor 15 (GDF-15) can serve as a biomarker for cardiovascular disease burden and risk. We evaluated a new, fully automated electrochemiluminescence immunoassay for measuring GDF-15. Methods: Six laboratories independently characterized the Elecsys ® GDF-15 assay (Roche Diagnostics) under routine conditions. Within-run precision (repeatability), within-laboratory precision (intermediate precision), and between-laboratory precision (reproducibility) were assessed. Plasma-serum sample correlation, reagent lot-to-lot reproducibility, and instrument comparisons were performed. The Elecsys assay was compared to a research immunoradiometric assay (IRMA) and a commercially available ELISA. GDF-15 concentrations were measured with the Elecsys assay in 739 apparently healthy individuals. Results: CVs for within-run and within-laboratory precision ranged from 0.7% to 7.7% and 1.7% to 8.6%, respectively, for samples containing 670–16039 ng/L. CVs for between-laboratory precision ranged from 7.1% to 8.9% (766–14289 ng/L). Recovery of GDF-15 was comparable for serum, Li-heparin plasma, K2 - and K3 -EDTA plasma, and citrated plasma, between 2 reagent lots, and on the cobas e 411 and cobas e 601 analyzers (Roche Diagnostics). GDF-15 concentrations in the clinically relevant range (400–3000 ng/L) measured with the Elecsys assay showed a good correlation and agreement with those measured by IRMA or ELISA. GDF-15 concentrations in apparently healthy individuals increased with age but did not vary by sex. Conclusions: The Elecsys GDF-15 assay demonstrates a robust analytic performance under routine conditions and provides an automated method for measuring GDF-15 concentrations in serum and plasma.